Warunkowa maksymalna strata jako miara ryzyka - Czernik, Tadeusz; Iskra, Daniel (Conditional maximal loss - an example of the first passage risk measure, 2006)
Conditional Maximal Loss (CML) has been proposed as a risk measure. It has been shown that CML has the ability to portfolio optimization. For a geometric brownian motion environment, analytical results was derived. A comparison to Conditional Value at Risk has been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 69-83